Predictors of Relapse to Alcohol and Substance Use: Are There Any Differences between 3 and 12 Months after Inpatient Treatment?. Issue 4 (8th August 2022) - Guliyev, Cavid; İnce-Guliyev, Ezgi and Ögel, Kültegin
ABSTRACT: Understanding the factors that lead to relapse is important for developing effective treatment strategies. The aim of this study is to examine sociodemographic and clinical factors that predict relapse 3 and 12 months after inpatient treatment in patients with alcohol and substance use disorders. 247 patients were included in the study. A sociodemographic data form and the Addiction Profile Index-Clinical Form (API-C) were filled out during the first days of hospitalization and relapse information was obtained through outpatient interviews. Logistic regression analysis was used to assess predictive factors. Rates of relapse for the 3 rd and 12 th months were 40.5% and 74.6%, respectively. Motivation to quit substance use, risk of depression, being on probation, and being employed predicted relapse within the 3-month period. At the 12 th month, substance use intensity and motivation to quit were the factors associated with relapse. To conclude, motivation to quit is critical to maintaining both early and sustained remission. Moreover, divergent factors may be relevant at different stages of treatment. Defining relapse predictors early in the process and being vigilant to the change in the needs of patients as the treatment continues may help to develop a more effective and focused treatment plan.